Insight into synergistic antioxidation mechanisms of butyl hydroxyanisole with common synthetic antioxidants - Jun Li; Jiali Chen; Yanlan Bi; Huifang Yang (Grain & Oil Science and Technology, 2022)
Butyl hydroxyanisole (BHA) is usually blended with other synthetic antioxidants to improve the antioxidative property due to synergistic antioxidation. However, the synergistic antioxidation mechanisms of BHA with synergists have not been revealed yet. Thus, the antioxidation of BHA with butylated hydroxytoluene (BHT), tert-butylhydroquinone (TBHQ), or propyl gallate (PG) was investigated in the 2,2-azobis(2-amidino-propane) dihydrochloride oxidizing system. The contents of BHA, BHT, TBHQ, PG, and transformation products were measured by high-performance liquid chromatography. Transformation products were identified with liquid chromatography-mass spectrometry and gas chromatography–mass spectrometry. Results showed that synergistic antioxidation occurred between BHA and BHT, TBHQ, or PG. The synergistic antioxidation effect of BHA and BHT was attributed to the regeneration of BHA by BHT. Transformation products of BHA and BHT (compounds 6 and 7, dimers of BHA and BHT) had little contribution due to the relatively low content (<0.6%). The synergistic antioxidation effect of BHA and TBHQ or BHA and PG was attributed to the protective mechanism of TBHQ on BHA. No transformation products were detected of BHA and TBHQ. Transformation products of BHA and PG (compounds 9 and 10, dimers of BHA and PG) had limited contribution due to the relatively low percentage of (<7%). Therefore, BHA and BHT performed competitive antioxidation, while BHA and TBHQ or PG performed protective antioxidation.